The righteous path of least resistance: Hermann Rauschning’s warning to the world - Leach, David Patrick (Kansas State University, 2022)
This report focuses on the life and career of Hermann Rauschning, who as a conservative, sought to enact political and economic reforms in his adopted home of Danzig during the tumultuous years of the early 1930s. When the German National Peoples’ Party (DNVP) could not adapt to the radicalization of German politics during the Weimar Republic, the party’s leadership and other members engaged with the National Socialist German Workers’ Party (NSDAP) hoping to gain the necessary support to maintain relevance. As the National Socialists rose to power, those in the DNVP saw their political influence waning. Hermann Rauschning switched political affiliations out of convenience instead of ideology by joining the Nazis because, with their ascendency, he saw an opportunity to enact the reforms his constituents, neighbors, and friends in Danzig needed to survive. However, the revolutionary machinery within Nazism proved too dangerous and nihilistic for Rauschning. He could no longer govern effectively because of Nazi interventions in Danzig. He felt forced to resign his post as President of the Senate of Danzig when he was ignored after asking for economic assistance and berated for refusing to arrest what local Nazi officials referred to as dissidents of the party. He fled through Europe and eventually to the United States where he settled on a farm outside Portland, Oregon for the remainder of his life. As a Nazi émigré, Rauschning authored eleven books and numerous articles where he warned the world of the dangers that Adolf Hitler and National Socialism posed to Western ideas of democracy.
Keywords: Hermann Rauschning; DNVP; Warning; Danzig; Nazi; World War Two